Efeitos da adrenomodulina no tratamento da hipertensão pulmonar induzida por microesferas em ovinos - Carvajal, Angie Paola Lagos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Accumulating evidence suggests that pulmonary vasoconstriction drives many of the haemodynamic disorders found in acute pulmonary embolism (APE). Because adrenomedullin induces pulmonary vasodilation and increases myocardial inotropism, the use of this peptide could minimize the pulmonary hypertension secondary to APE and improve cardiac output. This study examined the effects of adrenomodullin in a sheep model of APE. Under ketamine/midazolam anaesthesia, variables were recorded in nonembolized sheep treated with physiological saline (Control) and in sheep with APE induced by intravenous injection of microspheres (500 mg) treated with either intravenous physiological saline (Emb) or adrenomedullin (50 ng/kg/min) (Emb+Adm) for 30 min (n = 8 per group). Plasma concentrations of cyclic adenosine (cAMP) and guanosine monophosphate (cGMP) were determined by enzyme immunoassay. Compared to values recorded 30 min after induction of APE, adrenomedullin significantly (P < 0.05) decreased pulmonary vascular resistance index by 26% and significantly increased cardiac index by 28% with no impact on mean pulmonary artery pressure. Adrenomedullin significantly lowered systemic mean arterial pressure and systemic vascular resistance index by 24% and 40%, respectively. While significant increases in cAMP concentrations were observed with adrenomedullin (P < 0.05), cGMP levels were unaltered. Adrenomedullin induces systemic and pulmonary vasodilation in a microsphere model of APE. However, an anti-hypertensive effect of adrenomedullin on the pulmonary circulation may be offset by increased CI. These findings suggest that intravenous adrenomedullin should be used cautiously for treating pulmonary hypertension because of a significant impact on systemic circulation

A vasoconstrição pulmonar é responsável por grande parte dos distúrbios hemodinâmicos encontrados na embolia pulmonar aguda (EPA). A adrenomedulina, devido a sua ação vasodilatadora pulmonar e inotrópica positiva, poderia minimizar a hipertensão pulmonar e otimizar o índice cardíaco (IC) em indivíduos acometidos pela EPA. Objetivou-se avaliar os efeitos hemodinâmicos e respiratórios da adrenomedulina em um modelo de EPA induzida por microesferas em ovinos. Sob anestesia com cetamina/midazolam, mensuraram-se variáveis hemodinâmicas e respiratórias em ovelhas não embolizadas tratadas com solução salina fisiológica intravenosa (IV) (Controle) e em ovelhas com EPA induzida pela injeção IV de microesferas de silicone (500 mg), tratadas pela via IV com solução fisiológica (Emb) ou com adrenomedulina (50 ng/kg/min) (Emb+ADM) durante 30 min (n = 8 por grupo). As concentrações plasmáticas de monofosfato cíclico de adenosina (AMPc) e o monofosfato cíclico de guanosina (GMPc) foram determinadas por ensaio imunoenzimático. Comparado aos valores obtidos 30 min após da indução da EPA, a ADM diminuiu significativamente (P < 0,05) o índice de resistência vascular pulmonar em 26% e aumentou significativamente o IC em 28%, sem alterar a pressão média da artéria pulmonar. A adrenomedulina reduziu significativamente a pressão arterial média e o índice de resistência vascular sistêmica em 24% e 40%, respectivamente. Embora a concentração de AMPc tenha se elevado significativamente com a adrenomedulina (P < 0,05), os níveis de GMPc permaneceram inalterados. A adrenomedulina induz vasodilatação pulmonar e sistêmica na EPA induzida por microesferas em ovelhas. No entanto, o efeito anti-hipertensivo pulmonar da adrenomodulina foi prevenido pelo incremento do IC. A adrenomedulina IV deve ser empregada com cautela para o tratamento da hipertensão pulmonar secundária à EPA devido ao seu impacto sobre a circulação...
Effects of adrenomedullin treatment for pulmonary hypertension induced by microspheres in sheep
Keywords: Peptídeos microbianos; Embolia pulmonar; Hipertensão pulmonar; Monitorização hemodinamica; Ovino; Microesfera; Pulmonary hipertension